A metaphysics for freedom - Steward, Helen (Oxford : Oxford University Press, 2012)
Steward argues that determinism is incompatible with agency itself - not only the special human variety of agency, but also powers which can be accorded to animal agents. She offers a non-dualistic version of libertarianism, rooted in a conception of what biological forms of organisation might make possible in the way of freedom.
Includes index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Free will and determinism; Agent (Philosophy); Causation